2014
DOI: 10.1371/journal.pone.0098970
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Prevents Pyrrolizidine Alkaloid Clivorine-Induced Liver Injury in Mice by Elevating Body Defense Capacity

Abstract: Quercetin is a plant-derived flavonoid that is widely distributed in nature. The present study is designed to analyze the underlying mechanism in the protection of quercetin against pyrrolizidine alkaloid clivorine-induced acute liver injury in vivo. Serum transaminases, total bilirubin analysis, and liver histological evaluation demonstrated the protection of quercetin against clivorine-induced liver injury. Terminal dUTP nick end-labeling assay demonstrated that quercetin reduced the increased amount of live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 36 publications
2
24
0
1
Order By: Relevance
“…Several evidences have also revealed that acute CCl 4 intoxication increased circulating levels of inflammatory cytokines/chemokines, including interleukins, cytokines and nuclear factor-κB (NF-κB) [2,11,12,27]. Under normal physiological conditions, IκBα is an intracellular functional protein that acts on inhibiting the NF-κB transcription in the nucleus.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several evidences have also revealed that acute CCl 4 intoxication increased circulating levels of inflammatory cytokines/chemokines, including interleukins, cytokines and nuclear factor-κB (NF-κB) [2,11,12,27]. Under normal physiological conditions, IκBα is an intracellular functional protein that acts on inhibiting the NF-κB transcription in the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…Under normal physiological conditions, IκBα is an intracellular functional protein that acts on inhibiting the NF-κB transcription in the nucleus. When IκBα phosphorylation occurs, NF-κB transcription factors will bind to DNA sites to facilitate the transcription of many downstream genes encoding inflammation associated enzymes such as inducible nitric oxide synthase (iNOS), interleukin-1beta (IL-1β) and cyclooxygenase-2 (COX-2) [2,[11][12][13]. Excessive ROS induced by CCl 4 intermediates can also function as signaling messengers to NF-κB and ultimately lead to increased inflammatory cytokine production [2,3].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations